THE SOCIAL AND CULTURAL FUNCTIONS OF CHINESE RURAL SCHOOLS IN THE NEW ERA - YAHUI, WU; ABDUL WAHAB, NORWALIZA BINTI (International Journal of Research in Education Humanities and Commerce, 2023)
Chinese society is rural; rural education is an important part of China. The development of rural schools is not only a problem of China's basic education political revolution but also a problem directly related to the sustainable development of Chinese society. This paper is a literature review of rural schools' social and cultural functions from the Chinese documentary and literature. Multiple definitions of the term rural are provided. The findings are represented via different overarching themes. The findings reveal that rural schools can perform social and cultural functions if they are developed as an important component of rural construction in the new era, enhancing the cultivation and inheritance of rural culture, extensively carrying out vocational education to serve the rural revitalization strategy directly, and vigorously cultivating all-subject teachers with a local flavor.